2010
DOI: 10.1017/s0016756810000154
|View full text |Cite
|
Sign up to set email alerts
|

Diopsidites from a Neoproterozoic–Cambrian suture in southern India

Abstract: We report the occurrence and characteristics of diopsidite dykes and veins from the Palghat-Cauvery Suture Zone (PCSZ) marking the boundary between the Archaean Dharwar craton to the north and the Proterozoic Madurai Block to the south, which is considered as a trace of the Cambrian Gondwana suture zone in southern India. The diopsidites are composed predominantly of coarse crystals of diopside [Mg no. (100 Mg/(Mg+Fe tot )) up to 89] surrounded by retrograde calcic amphibole, plagioclase and phlogopite with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
(142 reference statements)
0
11
0
Order By: Relevance
“…Thus, we assume that the temperatures of the Voronezh Crystalline Massif diopsidite formation occurred at temperature from 600°C (veinlets) to 800°C (dykes). The circulation of Ca-enriched fluids within subduction-related setting has been reported in previous studies (Jan and Howie, 1981;Yang, 2006;Python et al, 2007Python et al, , 2011Bach and Klein, 2009;Santosh et al, 2010;Akizawa et al, 2011). The amphibolites adjacent to the diopsidites were subjected to diopsidization.…”
Section: Genesis Of Diopsiditesmentioning
confidence: 71%
See 4 more Smart Citations
“…Thus, we assume that the temperatures of the Voronezh Crystalline Massif diopsidite formation occurred at temperature from 600°C (veinlets) to 800°C (dykes). The circulation of Ca-enriched fluids within subduction-related setting has been reported in previous studies (Jan and Howie, 1981;Yang, 2006;Python et al, 2007Python et al, , 2011Bach and Klein, 2009;Santosh et al, 2010;Akizawa et al, 2011). The amphibolites adjacent to the diopsidites were subjected to diopsidization.…”
Section: Genesis Of Diopsiditesmentioning
confidence: 71%
“…12), Sr and LREE (Fig. Both the lower crust (Santosh et al, 2010;Akizawa et al, 2011) and upper mantle Akizawa and Arai, 2014) diopsidites exhibit similar petrographic and mineralogical characteristics, indicating their genetic coherence. Python et al (2007) suggested that seawater penetrated down to the mantle and provided the source for Ca, Sr and LREE.…”
Section: Genesis Of Diopsiditesmentioning
confidence: 93%
See 3 more Smart Citations